2015
DOI: 10.1007/s12306-015-0381-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personality psychology on outcome of total hip arthroplasty: a cross-sectional study on 69 patients

Abstract: Multidimensional Health Locus of Control can be considered a predictor of patient's satisfaction after an invasive surgical procedure as total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These findings do not necessarily mean a lack of correlation between worse surgical outcome and fibromyalgia syndrome. Indeed, we expect that a significant prevalence of fibromyalgia in patients referring to orthopedic surgeons for shoulder pain may emerge with specifically designed studies addressing this topic, based on the highly reported prevalence of fibromyalgia syndrome in the general population [3], on the evidence that the shoulder is among the most frequently affected regions in fibromyalgia syndrome [12], and on the evidence coming from lower-extremity joint replacement patients [15,18,28] and from other specialties such as gynecologic surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…These findings do not necessarily mean a lack of correlation between worse surgical outcome and fibromyalgia syndrome. Indeed, we expect that a significant prevalence of fibromyalgia in patients referring to orthopedic surgeons for shoulder pain may emerge with specifically designed studies addressing this topic, based on the highly reported prevalence of fibromyalgia syndrome in the general population [3], on the evidence that the shoulder is among the most frequently affected regions in fibromyalgia syndrome [12], and on the evidence coming from lower-extremity joint replacement patients [15,18,28] and from other specialties such as gynecologic surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Trevisan et al [35] conducted a cross-section study that was aimed at assessment of the relationship between pain sensation, clinical outcome, and subjective satisfaction, as well as multidimensional health locus of control (MHLC). Mean values of the study for all the respondents for the MHLC dimensions were IHLC 25.3, EHLC 23.5, and CHLC 18.9.…”
Section: Discussionmentioning
confidence: 99%
“…IRD patients have a higher risk of depression and other psychological diseases due to high tension and low self-esteem followed by the perceived impact of RA, fatigue, passive coping, pain, and physical disability [ 27 ]. Considering the relationship between personality psychology and expected clinical outcomes, counselling with a psychological team before surgery is recommended [ 28 ]. Future studies should also evaluate non-pharmacological management of these patients.…”
Section: Aspects Related To the Underlying Diseasementioning
confidence: 99%